THE EFFECT OF ELEVENIA TELEVISION ADVERTISEMENTS ON STUDENTS' BUYING INTEREST - Rama Dwissa Wiana; Dwika Lutfhi Permana; Janeru Kennedy (Gapenas Publisher, 2021)
The presence of television advertisements certainly causes a significant shock to the Indonesian advertising media landscape.The effective impact of repeated advertising exposure is to gain the attention and experience of the individual recipients who are exposed to the advertising message, and openly accept the messages they convey. In addition to paying attention to the wants and needs of its consumers, Elevenia also always introduces and instills an image for consumers of its brand by using various advertisements including television advertising media. The purpose of this study was to find out how much influence the variable